The Effect of Tertiary Butylhydroquinone Antioxidant on The Stability of Rubber Seed Biodiesel - Salma Fitri Annisa; Zulmanelis Darwis; Tritiyatma Hadinugrahaningsih (Chemistry and Materials, 2022)
This study aims to determine the effect of the addition of tertiary butylhydroquinone (TBHQ) antioxidants on the quality of biodiesel. Rubber seed biodiesel is synthesized through esterification and transesterification reactions, then biodiesel is characterized by different stages of adding TBHQ antioxidants before the esterification reaction and after the transesterification reaction. The usage of TBHQ antioxidants at the various stages of adding the process greatly affects the quality of biodiesel. The results showed that the addition of TBHQ 1000 ppm after transesterification was the most effective in slowing oxidative degradation by showing the lowest characteristics (acid number 0.64 mg KOH/g and peroxide value 33.91 meq O2/kg) for 3 weeks. All rubber seed biodiesel samples had kinematic density and viscosity according to the Indonesian National Standard (SNI) for 3 weeks except for the acid number only lasted 0 weeks.